2022
DOI: 10.1584/jpestics.d21-063
|View full text |Cite
|
Sign up to set email alerts
|

Insect growth regulators with hydrazide moiety inhibit strigolactone biosynthesis in rice

Abstract: S Supplementary materialStrigolactones (SLs) are carotenoid-derived plant hormones involved in several growth and developmental processes. Also, SLs are allelochemicals that induce the seed germination of root parasitic plants and the hyphal branching of arbuscular mycorrhizal fungi. In this study, to identify novel lead chemicals that inhibit SL biosynthesis, we evaluated the effect of agrochemicals on SL biosynthesis. We found that the diacylhydrazine insect growth regulator, chromafenozide, reduced the endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…[8][9][10] Recently, our group reported that insect growth regulators, chromafenozide and methoxyfenozide, were SL biosynthesis inhibitors. 11) In this study, we screened commercial agrochemicals for compounds that inhibit dark-induced hypocotyl elongation in Arabidopsis to find the novel BR action regulators and investigated the inhibitory activities of BRs by fenoxycarb.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Recently, our group reported that insect growth regulators, chromafenozide and methoxyfenozide, were SL biosynthesis inhibitors. 11) In this study, we screened commercial agrochemicals for compounds that inhibit dark-induced hypocotyl elongation in Arabidopsis to find the novel BR action regulators and investigated the inhibitory activities of BRs by fenoxycarb.…”
Section: Introductionmentioning
confidence: 99%